2017
DOI: 10.1002/2017jb014041
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow, heat production, and crustal temperatures in the Archaean Bundelkhand craton, north‐central India: Implications for thermal regime beneath the Indian shield

Abstract: Heat flow and heat production data sets constrain the crustal thermal structure in the 2.5–3.5 Ga Bundelkhand craton, the oldest cratonic core in northern Indian shield, for the first time and allow comparisons with the southern Indian shield. Temperature measurements carried out in 10 boreholes at five sites in the craton, combined with systematic thermal conductivity measurements on major rock types, yield low heat flow in the range of 32–41 mW m−2, which is distinct from the generally high heat flow reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Density of the basement rocks in the present study (range from 2,600 to 2,820 kg m −3 with an average of 2,720 kg m −3 ) is significantly lower than the basement rocks of the Killari borehole (range from 2,690 to 3,060 kg m −3 , with an average of 2,819 kg m −3 ) (Tripathi et al., 2012), but slightly higher than the range that is observed for the granitic rocks of the Dharwar Craton (2,520–2,730 kg m −3 with an average of 2,640 kg m −3 ) (Vijaya Raghava et al., 1977), as well as upper crustal granitic/gneissic rocks from different regions of the Indian shield (Chopra et al., 2018, 2020; Podugu et al., 2017; Ray et al., 2003). These studies yielded two important points: (a) the subsurface basement density is not the same in different parts of the DVP, which as corroborates the results of Tiwari et al.…”
Section: Discussionmentioning
confidence: 92%
“…Density of the basement rocks in the present study (range from 2,600 to 2,820 kg m −3 with an average of 2,720 kg m −3 ) is significantly lower than the basement rocks of the Killari borehole (range from 2,690 to 3,060 kg m −3 , with an average of 2,819 kg m −3 ) (Tripathi et al., 2012), but slightly higher than the range that is observed for the granitic rocks of the Dharwar Craton (2,520–2,730 kg m −3 with an average of 2,640 kg m −3 ) (Vijaya Raghava et al., 1977), as well as upper crustal granitic/gneissic rocks from different regions of the Indian shield (Chopra et al., 2018, 2020; Podugu et al., 2017; Ray et al., 2003). These studies yielded two important points: (a) the subsurface basement density is not the same in different parts of the DVP, which as corroborates the results of Tiwari et al.…”
Section: Discussionmentioning
confidence: 92%
“…In our preferred model of the initial steady‐state Indian thermal structure (shown in Figure 4), based on crustal data from the cratonic western Dharwar province (Roy & Mareschal, 2011), we use a 19‐km upper crust of tonalite‐trondhjemite‐granodiorite gneiss, overlying a 19‐km lower crust of mafic granulite, with radiogenic heat production of 1.1 and 0.36 μW m −3 , respectively, yielding a surface heat flux of 41.0 mW m −2 . Given the paucity of comprehensive data on crustal structure and heat production, we also trial three further models (Figure 4) for crustal heat production, based on values for the eastern Dharwar (Roy & Mareschal, 2011) and Bundelkhand (Podugu et al., 2017) provinces, all summarized in Table S1. Figure 5 then shows a comparison between our preferred model (western Dharwar) and the other three models.…”
Section: Thermal Modelingmentioning
confidence: 99%
“…The third row shows a model using a modified set of values for eastern Dharwar with a less‐depleted lower crust. The fourth row shows a model using the heat production values from the Bundelkhand craton in northern India (Podugu et al., 2017).…”
Section: Thermal Modelingmentioning
confidence: 99%
“…The Dhala impact structure, Shivpuri district, M.P., India since its confirmation as a bona fide terrestrial meteoritic impact structure based on the observation of diagnostic evidences of shock metamorphism (Pati, 2005;Pati et al, 2008;Pati et al, 2019) continues to attract the attention of geoscientific community. Gaur et al (2016) considered the impact melt breccia as "felsic volcanics" and further suggested that this "acid volcanic activity" is correlated to a global event at 1 Ga. Roy et al (2017) reported subsurface data from 14 boreholes out of 70 locations drilled (up to a depth of 476.55 m) in different parts of Dhala structure in search of uranium and the laudable extensive drilling activity by the Atomic Minerals Directorate for Exploration and Research, Govt. of India immensely helped in the better understanding of the impact cratering process at Dhala.…”
Section: Impact Cratering Researchmentioning
confidence: 99%
“…Li et al (2018) studied the impact melt breccia and reported the presence of reidite, a high pressure polymorph of zircon and further constrained the age of Dhala impact between 2.44 and 2.24 Ga, although both findings have been questioned (Pati et al, 2018). Podugu et al (2017) reported heat flow, heat production and crustal temperatures of BuC based on data collected from 10 borehole cores in five locations (one to the north of BTZ and four to the southern part). They observe a low heat flow (32-41 mWm -2 ) unlike AC but similar to Dharwar and other Archean Cratons worldwide.…”
Section: Impact Cratering Researchmentioning
confidence: 99%